2003
DOI: 10.1046/j.1365-2311.2003.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Clutch size in frugivorous insects as a function of host firmness: the case of the tephritid fly Anastrepha ludens

Abstract: Abstract. 1. Optimal clutch size theory predicts that individuals will oviposit the number of eggs that increases their fitness. In Anastrepha ludens Loew (Diptera: Tephritidae), females oviposit larger clutches in unripe (firm) fruits than in ripe (soft) fruits. The following hypotheses were tested: (1) Using fruit firmness as an indicator of fruit quality, A. ludens females vary the number of eggs per clutch every time they reach an oviposition decision. (2) Maximising offspring survival with respect to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 40 publications
6
52
3
1
Order By: Relevance
“…Aluja et al (2001) observed that the presence of hosts and their volatile substances are important for ovarian maturation of A. obliqua. In addition, the presence of ripe fruits also influences the females' oviposition decision, probably due to the sugar content (Fernandes-da-Silva & Zucoloto 1997, Díaz-Fleischer & Aluja 2003. So, according to our results, the protein is the nutrient that most stimulates oviposition.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Aluja et al (2001) observed that the presence of hosts and their volatile substances are important for ovarian maturation of A. obliqua. In addition, the presence of ripe fruits also influences the females' oviposition decision, probably due to the sugar content (Fernandes-da-Silva & Zucoloto 1997, Díaz-Fleischer & Aluja 2003. So, according to our results, the protein is the nutrient that most stimulates oviposition.…”
Section: Discussionsupporting
confidence: 52%
“…We believe that the discussion presented by Díaz-Fleischer and Aluja (2003) regarding the oviposition behavior of Anastrepha ludens (Loew) is also applicable to what was observed for A. obliqua. Ripe fruits, with higher sugar content, are more attractive and susceptible to predation by vertebrates, occasionally leading to larva's death.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, a polyphagous insect with high behavioral adaptability, as A. obliqua, may keep a large number of hosts. Several authors (Carey et al 1986;Prokopy & Reynolds 1998;Díaz-Fleischer & Aluja 2003a, 2003b) and the present study have reported the plasticity of fruit flies concerning their oviposition behavior strategies. In this sense, further investigations on the factors related to this behavior are needed.…”
Section: Discussionsupporting
confidence: 52%
“…In phytophagous insects that lay eggs in discrete packets of food, there is a tendency to select resources of adequate quality to ensure larval development (Diaz-Fleischer and Aluja 2003a). A wide variety of factors seem to influence host selection by fruit flies (Balagawi et al 2005).…”
Section: Introductionmentioning
confidence: 99%